THE APPLICATION OF PATTERN MATCHING ALGORITHM AND DYNAMIC PROGRAMMING FOR DETECTION MUSIC SIMILARITY - Ida Bagus Nyoman Pascima (Universitas Pendidikan Ganesha, 2012)
Art work has various meanings based on the viewers. Every art work is created by human’s insting which has value and should be praised. The right of intelectuality or “HAKI” is the means to price and save every art which is coming from human’s insting. “HAKI” can price a music as an art. The music flagiarism causes the ancienty in the musician side because it is not beneficial for them in a side of “HAKI”. However, there are some views and supports toward that flagiarism such as similar idea, inspirations, admire the work that was traced, and so forth. People are difficult to know for certainly the similarity or resemblance to the work of art even more amount of music. This thing then becomes a case in a musical flagiarism. Based on these problems occurred with an idea to utilize a computerized system to find a resemblance to a piece of music. A computerized system used for detecting the level of resistance factors in a long time, matching the constant accuracy and high speed. This system is based on pattern of human’s thinking (algorithm) to detect musical of similarity. This system was developed by PHP script, AJAX as the programming language, and MySQL as the database processing. The result of the system can use algorithm as the pattern of human’s thinking for detecting musical similarity. Beside that, this system is also able to collect the music based on some criteria. This system can be working on monophonic music. This system can help the people in detecting the music similarity and as the solution of the problem so that the music flagiarism can be minimalized.